Positive maternal interaction behavior moderates the relation between maternal anxiety and infant regulatory problems - Richter, Nina; Reck, Corinna (Infant behavior and development, 2013)
Regulatory problems in infancy are determined by different risk factors. This study aims to examine how psychosocial risk factors are connected, and how they impact the early regulatory ability of 3-month-old infants. In a sample of 57 mother-infant dyads, maternal anxiety and infant crying, sleeping and feeding habits were assessed. As a possible moderator, the role of positive maternal behavior was analyzed by videotaping face-to-face interactions. During the interaction, interactive stress was provoked with the face-to-face still-face paradigm (FFSF). Thus, this study differentiated between the effects of maternal behavior in both an ordinary play context, as well as a stressful interaction context. Results revealed that the relation between maternal anxiety and infant regulatory problems in crying and sleeping varied as a function of positive maternal engagement in stressful situations. However, a significant moderation effect influencing infant feeding problems could not be demonstrated. These findings stress the importance of positive maternal interaction behavior in at least some parts of regulatory adjustment of at-risk infants.
Gesehen am 11.01.2022